The Use of Interactive Power Point Media to Improve Arabic Learning Outcomes - Bagas Irawan; Daniel Robert (IJAS: International Journal of Arabic Studies, 2026)
This study examines the effectiveness of interactive PowerPoint media in improving students’ Arabic learning outcomes, particularly at the elementary level. It employs a quantitative approach using a pre-experimental design with a one-group pretest–posttest model. The participants consisted of elementary-level students who were selected through purposive sampling. Data were collected through structured tests administered before and after the implementation of the interactive PowerPoint-based instruction. The analysis involved both descriptive and inferential statistics, including the calculation of mean scores and significance testing to measure learning improvement. The findings reveal a statistically significant increase in students’ posttest scores compared to their pretest results. This improvement indicates that interactive PowerPoint media effectively enhances students’ vocabulary acquisition, reading comprehension, and overall engagement during the learning process. Additionally, the use of multimedia elements such as animations, visuals, and interactive quizzes contributed to a more engaging and student-centered learning environment. Therefore, this study concludes that interactive PowerPoint is a practical and effective instructional tool for enhancing Arabic language learning outcomes.